2021 IEEE International Workshop on Biometrics and Forensics (IWBF) 2021
DOI: 10.1109/iwbf50991.2021.9465085
|View full text |Cite
|
Sign up to set email alerts
|

On the Applicability of Synthetic Data for Face Recognition

Abstract: Face verification has come into increasing focus in various applications including the European Entry/Exit System, which integrates face recognition mechanisms. At the same time, the rapid advancement of biometric authentication requires extensive performance tests in order to inhibit the discriminatory treatment of travellers due to their demographic background. However, the use of face images collected as part of border controls is restricted by the European General Data Protection Law to be processed for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…To balance this trade-off, a truncation factor can be used to stabilise the sampling: the truncated latent code w is calculated as w = w + ψ(w − w) where w indicates the latent spaces' center of mass and ψ denotes the truncation factor. Following the empirical analysis of Zhang et al [9], we choose a truncation factor of ψ = 0.75. In [9], the authors have shown that the biometric performance of synthetic samples generated with StyleGAN and StyleGAN2 are similar and comparable to bona fide images from FRGC v2.0 [23].…”
Section: Synthetic Image Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…To balance this trade-off, a truncation factor can be used to stabilise the sampling: the truncated latent code w is calculated as w = w + ψ(w − w) where w indicates the latent spaces' center of mass and ψ denotes the truncation factor. Following the empirical analysis of Zhang et al [9], we choose a truncation factor of ψ = 0.75. In [9], the authors have shown that the biometric performance of synthetic samples generated with StyleGAN and StyleGAN2 are similar and comparable to bona fide images from FRGC v2.0 [23].…”
Section: Synthetic Image Generationmentioning
confidence: 99%
“…Following the empirical analysis of Zhang et al [9], we choose a truncation factor of ψ = 0.75. In [9], the authors have shown that the biometric performance of synthetic samples generated with StyleGAN and StyleGAN2 are similar and comparable to bona fide images from FRGC v2.0 [23]. Hence, this work uses StyleGAN for generating synthetic base images to enable the implementation of PCA-FR-Guided sampling to operate within the framework of InterFaceGAN [25].…”
Section: Synthetic Image Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether synthetic biometric data does realistically simulate real world applications, is an question that requires further investigations. [55].…”
Section: Hufhqwdjhmentioning
confidence: 99%
“…Motivated by the above-mentioned challenges, the use of synthetic data in biometrics has recently attracted attention. Zhang et al [47] investigated the behavior of face image quality assessment methods on synthetic images created by StyleGAN [15] and StyleGAN2 [16] and compare the face image quality values with those of authentic face images. Another biometric use case based on synthetic data that has Fig.…”
Section: Introductionmentioning
confidence: 99%